IMPLEMENTASI QANUN NOMOR 11 TAHUN 2002 SEBAGAI UPAYA DALAM MENCIPTAKAN KETENTRAMAN DAN KENYAMANAN BERIBADAH SHALAT JUM’AT DI KOTA BANDA ACEH - A.djalil, Roslina; adnin, Adnin; jasmadi, jasmadi (Institut Agama Islam Sahid (INAIS) Bogor, 2024)
Aceh Provincial Qanun Number 11 of 2002 Article 8 paragraph (1) Every Muslim who does not have a shar'i excuse is obliged to perform Friday prayers; paragraph (2) Every person, government agency, business entity and / or community institution is obliged to stop activities that can hinder / interfere with Muslims performing Friday prayers. This research has a very important urgency in an effort to realise Islamic Sharia in a kaffah manner in the city of Banda Aceh in addition, as an effort of the city government in creating peace and comfort for the community in performing Friday prayers in the city of Banda Aceh. The purpose of this study is to analyse and evaluate the extent of the implementation and obstacles of the policy to stop all activities before the Friday prayer service in Banda Aceh City. In addition, this study also aims to provide recommendations for policies in overcoming the obstacles and challenges faced by the Banda Aceh City Wilayatul Hisbah police in carrying out the tasks of socialisation, supervision and guidance to the community. This research method is a qualitative descriptive approach using Marille S. Grindle's theory of public policy implementation. In this study the data was analysed using data reduction techniques, data presentation, and conclusion drawing. The results of the research are expected to produce implications that can support the implementation of Islamic law in Banda Aceh City. All the results of this research can make a real contribution to efforts to increase public legal awareness. Thus, this research has great urgency in supporting the transformation of changes in the attitude of the community and business actors to obey and obey, and is expected to be able to make a positive contribution in efforts to improve the quality of legal services for the community. Keywords: Implementation; Policy; Order; Convenience of Worship; Shalat Jumat